APPLICATION OF MULTI-CRITERIA PROMETHEE METHOD TO ASSIST CHARACTER SELECTION IN THE ENDLESS RUNNER GAME - Nurrahma, Alfina; Nugroho, Fresy; Buditjahjanto, I.G.P. Asto; Pebrianti, Dwi; Hammad, Jehad A.H.; Fachri, Moch; Lestari, Tri Mukti; Maharani, Dian; Prakasa, Aji Bagas (Jurnal Teknik Informatika (Jutif), 2024)
The endless runner game is one of the most popular game genres, but selecting the optimal character for different map challenges poses a significant problem for players. In this context, this research was conducted to help select characters in the endless runner game using the PROMETHEE method. This selection is recommended based on the weight and difficulty of each map which varies, including the rice field map, road map and alley map. The implementation of calculating character recommendations uses the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) method with the highest score as the best ranking. Rank suitability can be determined by comparing the PROMETHEE method with the TOPSIS method on 15 characters alternatives with 6 criteria. As a result, the PROMETHEE method has significant value, but some still have the same best ranking as the TOPSIS method. Furthermore, usability testing was carried out on 57 respondents using the System Usability Scale (SUS) with an overall score from the evaluation of 78,8. The final score obtained based on the acceptance scale was included in the category suitable for use.